PERANAN PANCASILA DALAM MENUMBUHKAN KESADARAN NASIONALISME GENERASI MUDA DI ERA GLOBAL - Irhandayaningsih, Anna (Faculty of Humanities, Diponegoro University, 2012)
Indonesian as a nation state cannot avoid the challenges of globalization, but by adhering to the Pancasila as its guiding principles, Indonesia will be able to maintain its existence and identity. This paper argues that nurturing nationalistic spirit within the mind of young generation since times of childhood will make them more resilient to the negative influence and moral decadence rampant in the era globalization. Thus, by strengthening the morality and ethics through Pancasila education, the young generation of Indonesia will be more equipped to face globalization and maintaining Indonesian identity at the same time. Keywords: Pancasila, globalization, young generation, nationalism